Considerate Typography; How to Write and Publish a Scientific Paper; Women and Graphic - A Beginner's Kit - Myrna Daly; James W. King (Journal of Applied Communications, 1984)
Reviews of "Considerate Typography," by Jan White; How to Write and Publish a Scientific Paper, by Robert A. Day ; "Women and Graphics - A Beginner's Kit," special issue of The Tribune: A Women and Development Quarterly.